Students' perception of the strengths and weaknesses of the inclusive educational model of Brazilian municipal public schools - Capellini, Vera; Muñoz-Martínez, Yolanda; Gómez Puerta, Jose Marcos; Reis, Verônica Lima dos; Rocha, Eduardo Pimentel da (Frontiers in Education, 2024)
Brazil is a signatory of important documents that advocate the promotion and access to equitable, inclusive, and quality education. However, the construction of inclusive policies, practices, and cultures has been little discussed in the country, making difficult the process of educational inclusion of children with specific educational needs. This study aimed to investigate the perception of 6- and 7-year-old Brazilian students about the strengths and weaknesses of the inclusive educational model of municipal public schools in a city in Brazil. The Index for Inclusion was used to investigate children's perceptions considering the three things they like most about school and the three things they dislike. Data was analyzed qualitatively through content analysis, using prefixed categories created according to the children's answers to the Index (strengths and weaknesses), categorized considering the dimensions and subdimensions assessed by the Index. The results pointed out that children perceive the infrastructural and urban barriers present in their context, which are considered weaknesses for developing inclusive policies, practices, and cultures in their school contexts. On the other hand, they do not show attitudinal barriers, that is, they do not judge others for their differences. Thus, working on differences, from the first school stage, to build a positive relationship between children and the development of practices and an inclusive school can benefit the construction of a school community free of segregating values present in our culture, contributing to the development of inclusive policies, practices, and cultures in school environments.